Cerebrospinal Fluid Flow Cytometry in Pediatric Acute Lymphoblastic Leukemia: A Multicenter Retrospective Study in China - Songji Tu; Kunlong Zhang; Chenzhu Liu; Ningling Wang; Jinhua Chu; Linhai Yang; Zhiwei Xie; Lingling Hang; Jun Li; Wenyu Yang; Xiaofan Zhu (Cancer Medicine)
ABSTRACT Objective The central nervous system (CNS) is a frequent site of relapse in childhood acute lymphoblastic leukemia (ALL). This study aims to investigate the utility of cerebrospinal fluid (CSF) flow cytometry in detecting CNS infiltration and relapse. Methods Flow cytometry was used to detect CSF leukemia cells, and patients were categorized into the CSF Flow+ and CSF Flow− groups. The primary outcome was the cumulative incidence of relapse (CIR) in the CSF Flow+ and CSF Flow− groups. Results A total of 1301 patients were enrolled, 159 patients (12.2%) showed positive CSF flow cytometry results. The CNS Flow+ patients exhibited significantly higher rates of any CNS relapse (22.5% vs. 0.2%, p < 0.01) and isolated CNS relapse (10.7% vs. 0%, p < 0.01) compared to CNS Flow− patients. Cox regression analysis revealed that risk factors for isolated CNS relapse included a positive result of D46 minimal residual disease (MRD) and CSF Flow+ at a non‐initial diagnosis. For any CNS relapse, the significant risk factors were CSF Flow+ at the initial diagnosis and CSF Flow+ at a non‐initial diagnosis. Conclusions CSF flow cytometry may have clinical utility in detecting CNS infiltration among pediatric ALL patients. It could contribute to more effective risk stratification and treatment adjustments and potentially reduce the risk of CNS relapse.